A Morettian literary atlas of Naguib Mahfouz's Cairo in three early realist novels: Cairo modern, Khan al-Khalili, and Midaq alley - Sundberg, Paul A. (AUC Knowledge Fountain, 2015)
This thesis includes a variey of “literary map experiements” on a dataset of mappable, non-generic, places found in three early realist “Cairo novels” by Naguib Mahfouz: Cairo Modern (1945), Khan al-Khalili (1946) and Midaq Alley (1947) and analyses of the mapped results. Experiments in the “atlas” are conducted on each novel separately and – in a more ‘distant” reading – on combinations of the three novels. The methodology is one originated by Stanford literary historian Franco Moretti in his Atlas of the European Novel 1800-1900 and Graphs, Maps, Trees: Abstract Models for a Lierary History. To the researcher’s knowledge, this is the first time Moretti’s map methodology has been applied to Arab realist literature. The final discussion section compares places in the author’s own life up to 1947 with those included in the three novels. The original dataset, included in the appendices as a series of spreadsheets, is based on AUC Press’s English translations of the three novels and offers lists of “Major Plot Places,” “All Mentioned Places” in both alphabetical and frequency order, and autobiographical places mentioned by the author in al-Ghitani’s Mahfouz Dialogues.